IMPLEMENTASI STANDAR PENILAIAN PENDIDIKAN DI SDN NAGASARI 1 KARAWANG - Rafik Ramdani; Syifa Nuralvia Rahmah; Rifani Alina Syamsi; Hinggil Permana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Educational assessment is a crucial element in the learning process, especially at the elementary school level, serving as the initial foundation for developing students' character, knowledge, and skills. This study aims to describe the implementation of national educational assessment standards at SDN Nagasari 1 Karawang and identify challenges and efforts made to improve assessment quality. Using a descriptive qualitative approach, data were collected through observations and in-depth interviews with teachers and the principal. The results indicate that the school has implemented comprehensive assessments covering aspects of attitudes, knowledge, and skills using various instruments, such as written tests, assignments, observations, and portfolios. However, time constraints and technical constraints in the use of digital applications remain challenges. The principal's support and collaboration between teachers are crucial factors in supporting successful implementation. This study contributes as material for internal school evaluations and as a reference in developing a more effective and adaptive assessment system to meet current demands